Núcleos de acessibilidade nas instituições de ensino superior brasileiras: produções acadêmicas entre 2008-2020 nas plataformas CAPES e BDTD - Araújo, Rodrigo Duarte (2024)
Master's research, carried out within the scope of the State, Policies and Management of Education Line of the Postgraduate Program in Education at the Federal University of Uberlândia, is part of a macro research carried out by the Group of Studies and Research in Policies and Practices in Education Special and Inclusion – Gepepes. Its object is the following productions: Accessibility centers in Brazilian institutions between 2008-2020 on the Capes Portal and the Digital Library of Theses and Dissertations (BDTD). The main objective is to investigate what has been researched and studied about Accessibility Centers, in order to contribute to the consolidation of this universe within the academic field. The specific objectives are to discuss the academic literature about Accessibility Centers in Higher Education, according to the works registered in the Database of Theses and Dissertations and Capes; highlight what research was published in the period between 2008-2022 on the Capes Portal and BDTD for this field of studies, as well as the advances, achievements and challenges in the subject, mapping which regions of the country carried out these studies on inclusive education and related policies to the Accessibility Centers. This research established a methodology of descriptive work, surveying art, characterized by a discussion of a qualitative approach, of a basic nature, which starts from readings of the dissertations and theses that make up the corpus of analysis. It is believed that this research will contribute to expanding discussions about Accessibility Centers in Brazilian institutions to guarantee the entry and retention of students, ensuring the right of people with disabilities to Higher Education. In general, we identified, in the time frame of the research, a number of 24 works that directly dealt with our theme, 20 of which were dissertations and 4 theses. The discussion categories constructed from the organization of the data were: Inclusion Policies in Higher Education; Implementation of Accessibility Centers at IFES and Permanence of public Special Education students at IFES. It was identified that: a) policies in the area need to promote equal opportunities and ensure that all students, regardless of their physical, sensory, cognitive or other capabilities, have opportunities to learn and develop to their maximum potential; b) the main accessibility difficulties in Higher Education are related to ensuring equal opportunities for all students. Based on these challenges, we reinforce through discussions that Accessibility Centers in Higher Education are fundamental in promoting inclusion and guaranteeing equal opportunities for all students. It was evident that the Accessibility Centers help to eliminate physical, pedagogical and attitudinal barriers that could impede the full participation of these students. The research therefore highlights the need for more bibliographic and empirical studies that address the importance of Accessibility Centers in these academic spaces, as well as offering support for evaluations and improvements in the work that is already being developed in the institutions.